2024
DOI: 10.3390/jcdd11020062
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac and Renal Fibrosis, the Silent Killer in the Cardiovascular Continuum: An Up-to-Date

Traian Chiuariu,
Delia Șalaru,
Carina Ureche
et al.

Abstract: Cardiovascular disease (CVD) and chronic kidney disease (CKD) often coexist and have a major impact on patient prognosis. Organ fibrosis plays a significant role in the pathogenesis of cardio-renal syndrome (CRS), explaining the high incidence of heart failure and sudden cardiac death in these patients. Various mediators and mechanisms have been proposed as contributors to the alteration of fibroblasts and collagen turnover, varying from hemodynamic changes to the activation of the renin–angiotensin system, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 103 publications
0
1
0
Order By: Relevance
“…Fibroblast Growth Factor-23 (FGF-23) is increased in patients with CKD, and it has been shown to alter renal flow-mediated vascular regulation and arterial stiffness. An in vitro study on human atrial myocardiocytes demonstrated a cardiac profibrotic role and induction of myocardial hypertrophy [34]. Deficiency of Klotho protein-positive myocardial regions, the co-receptor of FGFR1, demonstrated in myocardial autoptic samples of dialysis patients with high FGF-23 serum levels, has been associated with higher cardiac fibrosis and ventricular hypertrophy with an inversely proportional relation [35].…”
Section: Pathophysiology Of Chronic Kidney Disease In Hfpefmentioning
confidence: 99%
“…Fibroblast Growth Factor-23 (FGF-23) is increased in patients with CKD, and it has been shown to alter renal flow-mediated vascular regulation and arterial stiffness. An in vitro study on human atrial myocardiocytes demonstrated a cardiac profibrotic role and induction of myocardial hypertrophy [34]. Deficiency of Klotho protein-positive myocardial regions, the co-receptor of FGFR1, demonstrated in myocardial autoptic samples of dialysis patients with high FGF-23 serum levels, has been associated with higher cardiac fibrosis and ventricular hypertrophy with an inversely proportional relation [35].…”
Section: Pathophysiology Of Chronic Kidney Disease In Hfpefmentioning
confidence: 99%